119Sn Mössbauer and magnetization studies of the Heusler alloy Ni2Mn1.48Sn0.52. (January 2023) - Amako, Y.; Tanaka, S.; Nakashima, M.; Eto, T.; Adachi, Y.; Kanomata, T.
Abstract: The results of experimental investigations of the crystal structure, magnetization and Mössbauer spectroscopy of the Heusler alloy Ni2 Mn1.48 Sn0.52 are reported. The alloy undergoes the martensitic transition from the L 21 -type cubic structure into 4 O -type orthorhombic structure with a thermal hysteresis of ∼23 K. The martensitic transition temperature T M is 309 K. The Curie temperature in the austenitic phase T C A of Ni2 Mn1.48 Sn0.52 is found to be 316 K. The Mössbauer spectra from the high temperature paramagnetic state at 330 K and the martensitic state at 283 K were both singlets, showing a typical paramagnetic feature in the narrow temperature range just below T M . With further decrease of temperature, the ferromagnetic ordered state also appears in the martensitic phase. The Curie temperature in the martensitic phase T C M is found to be 256 K. Furthermore, the exchange bias effect is observed in the temperature range 1.8 K ≤ T  ≤  T B (∼130 K), where T B is an exchange bias blocking temperature. The values of a hyperfine magnetic field at Sn nuclei of Ni2 Mn1.48 Sn0.52 fall significantly below the molecular magnetic field approximation for S  = 1. On the basis of the experimental results, the electronic and magnetic properties of Ni2 Mn1.48 Sn0.52 are discussed. Highlights: The Heusler alloy Ni2 Mn1.48 Sn0.52 undergoes the martensitic transition at 309K. Sn Mössbauer spectrum just below the martensitic transition temperature is singlet. The Curie temperature in the martensitic phase is found to be 256 K. The exchange bias effect is observed in the temperature range 1.8 K ≤ T ≤∼130K. Temperature variation of Sn hyperfine fields falls below the molecular field approximation.